Bioisosteric Modification of To042: Synthesis and Evaluation of Promising Use‐Dependent Inhibitors of Voltage‐Gated Sodium Channels. (5th October 2021) - Milani, Gualtiero; Cavalluzzi, Maria Maddalena; Altamura, Concetta; Santoro, Antonella; Perrone, Mariagrazia; Muraglia, Marilena; Colabufo, Nicola Antonio; Corbo, Filomena; Casalino, Elisabetta; Franchini, Carlo; Pisano, Isabella; Desaphy, Jean‐François; et al.
Abstract: Three analogues of To042, a tocainide‐related lead compound recently reported for the treatment of myotonia, were synthesized and evaluated in vitro as skeletal muscle sodium channel blockers possibly endowed with enhanced use‐dependent behavior. Patch‐clamp experiments on hNav1.4 expressed in HEK293 cells showed that N ‐[(naphthalen‐1‐yl)methyl]‐4‐[(2, 6‐dimethyl)phenoxy]butan‐2‐amine, the aryloxyalkyl bioisostere of To042, exerted a higher use‐dependent block than To042 thus being able to preferentially block the channels in over‐excited membranes while preserving healthy tissue function. It also showed the lowest active transport across BBB according to the results of P‐glycoprotein (P‐gp) interacting activity evaluation and the highest cytoprotective effect on HeLa cells. Quantum mechanical calculations and dockings gave insights on the most probable conformation of the aryloxyalkyl bioisostere of To042 in solution and the target residues involved in the binding, respectively. Both approaches indicated the conformations that might be adopted in both the unbound and bound state of the ligand. Overall, N ‐[(naphthalen‐1‐yl)methyl]‐4‐[(2, 6‐dimethyl)phenoxy]butan‐2‐amine exhibits an interesting toxico‐pharmacological profile and deserves further investigation. Abstract : Proper neural activity : A bioisosteric replacement approach allowed the identification of a use‐dependent sodium channel blocker (17 a ) with low P‐glycoprotein‐mediated active transport across the blood‐brain barrier and a cytoprotective effect on HeLa cells. The target residues involved in binding hNav1.4 were identified by molecular docking studies.